2022
DOI: 10.1002/bab.2405
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitive colorimetric aptasensor based on short DNA aptamer and its application to screening for paraquat residues in agricultural soil

Abstract: Paraquat is a widely used herbicide for controlling weeds and grasses in agriculture, and its contaminated residues in agricultural areas are of increasing concern. This work reports the development of the sensitive and easy‐to‐use colorimetric aptasensor for screening paraquat residues in agricultural soil. The short DNA fragments derived from the original aptamer were analyzed for their capability to interact with paraquat by molecular dynamic simulation. The paraquat‐aptasensor was developed using the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This work outperforms a colorimetric assay that used the same aptamer, in terms of LOD and linear range. Recently, Kongpreecha et al, developed a colorimetric-based aptasensor with a shorter length DNA aptamer enabling the LOD of 2.76 nm. Furthermore, when compared to other techniques such as chromatography (GCMS), electrochemistry, and fluorescence, , our work has a lower LOD.…”
Section: Resultsmentioning
confidence: 99%
“…This work outperforms a colorimetric assay that used the same aptamer, in terms of LOD and linear range. Recently, Kongpreecha et al, developed a colorimetric-based aptasensor with a shorter length DNA aptamer enabling the LOD of 2.76 nm. Furthermore, when compared to other techniques such as chromatography (GCMS), electrochemistry, and fluorescence, , our work has a lower LOD.…”
Section: Resultsmentioning
confidence: 99%
“…The reference aptamer used in this study, known as R1 aptamer, is derived from the truncated aptamer reported in a previous study (5 0 -CGAGCGTTG-3 0 ). 20 Additionally, a series of aptamers with 2-5 repeats of paraquat binding sites were designed and labelled as R2-R5. To assess the binding capabilities of these aptamers to paraquat, a SYBR Green I competitive assay was conducted.…”
Section: The Determination Of the Binding Capability Of The Designed ...mentioning
confidence: 99%
“…The optimized pH was dened as the pH value that yielded the maximum absorbance ratio between A 650 and A 525 . Additionally, the optimization of temperature was determined by incubating AuNPs (7 nM) and aptamer (25 nM) at different temperatures (20,25,30,35, and 40 °C) for 30 min. Then, paraquat (50 nM) was added and incubated for an additional 30 min.…”
Section: Optimization For Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aptasensor is the aptamer‐based biosensor in which an aptamer is a key component for the specificity and accuracy of target detection, and an aptamer can detect diverse‐sized targets ranging from a small molecule 10 to a whole cell 11 . Aptamers are short single‐stranded DNA or RNA oligonucleotides, and their molecular structures are critical for binding affinity and selectivity to the target molecules via noncovalent interactions 12 .…”
Section: Introductionmentioning
confidence: 99%